ANALISIS PENGELOLAAN DANA DESA TAHUN ANGGARAN 2021 UNTUK PEMBERDAYAAN MASYARAKAT - Muhammad Yanwar Darmadi Putra; Budi Puspo Priyadi; Nina Widowati (Journal of Public Policy and Management Review, 2023)
Villages as the spearhead of national development have broad autonomy to improve the welfare of their people. This is in accordance with the substance of Village Law Number 6 of 2014 to provide wider autonomy to villages so that they can progress and be independent through village funds. Based on the Regulations of the Minister of Villages, Development Regions Disadvantaged, and Transmigration Republic of Indonesia Number 13 Year 2020 about Priorities Use of Village Funds Year 2021explained that priority usage village funds for the 2021 fiscal year are focused on community empowerment. Tarubatang Village, seen from the allocation of village fund costs for the 2021 fiscal year, is not in accordance with existing regulations because village funds for community empowerment are still small. In fact, the welfare of the people in Tarubatang Village has decreased in the last three years as evidenced by a decrease in poverty. The aim of this research is to determine the management of village funds for the 2021 fiscal year for community empowerment in Tarubatang Village and the factors that influence its management. This research uses village fund management theory. The method used in this research is descriptive qualitative. The results of this research show that from the analysis of village fund management starting from the planning, implementation and reporting stages, it is known that the cause of non-compliance with existing regulations is due to the community's lack of understanding of village development and hamlet consultation mechanisms that do not comply with regulations. Factors that influence the management of village funds for empowerment include human resources from village officials, the quality of the population, and openness of village information.